A subcortical network for implicit visuo-spatial attention: Implications for Parkinson's Disease. (August 2021) - Esposito, Matteo; Tamietto, Marco; Geminiani, Giuliano Carlo; Celeghin, Alessia
Abstract: Recent studies in humans and animal models suggest a primary role of the basal ganglia in the extraction of stimulus-value regularities, then exploited to orient attentional shift and build up sensorimotor memories. The tail of the caudate and the posterior putamen both receive early visual input from the superficial layers of the superior colliculus, thus forming a closed-loop. We portend that the functional value of this circuit is to manage the selection of visual stimuli in a rapid and automatic way, once sensory–motor associations are formed and stored in the posterior striatum. In Parkinson's Disease, the nigrostriatal dopamine depletion starts and tends to be more pronounced in the posterior putamen. Thus, at least some aspect of the visuospatial attention deficits observed since the early stages of the disease could be the behavioral consequences of a cognitive system that has lost the ability to translate high-level processing in stable sensorimotor memories.